Interaction of arsenic with biochar in soil and water: A critical review. (March 2017) - Vithanage, Meththika; Herath, Indika; Joseph, Stephen; Bundschuh, Jochen; Bolan, Nanthi; Ok, Yong Sik; Kirkham, M.B.; Rinklebe, Jörg
Abstract: Biochar exhibits a great potential to act as a universally applicable material for water and soil remediation due to extensive availability of feedstocks and favorable physio-chemical surface characteristics; nevertheless, studies related to its application on the remediation of toxic metalloids are relatively rare. Hence, this review highlights biochar production technologies, biochar properties, and recent advances in the removal and immobilization of a major metalloid contaminant, As in water and soil. It also covers surface modification of biochars to enhance As removal and microbial properties in biochar amended soil. Experimental studies related to the adsorption behaviors of biochar and the underlying mechanisms proposed to explain them have been comprehensively reviewed. Compared to the number of research publications in SCOPUS database on "Biochar+Water" (≈1290 – Scopus), the attention drawn to examine the behavior of biochar on the remediation of As is limited (≈85 - Scopus). Because of the toxicity of As, the subject urgently needs more consideration. In addition to covering the topics listed above, this review identifies research gaps in the use of biochar as an adsorbent for As, and proposes potential areas for future application of biochars.